Vitamin Deficiency-Induced Neurological Diseases of Poultry - Burgos, Sigfrido; Bohorquez, Diego V.; Burgos, Sergio A. (International Journal of Poultry Science, 2006)
Vitamins are organic compounds distinct from fats, carbohydrates and proteins, naturally found in most foods items in minute amounts for normal physiological function. Their essentiality in poultry nutrition is evidenced by diverse deficiency symptoms that manifest when they are lacking. They are intimately involved in a series of roles in organisms as antioxidant molecules, modulators of gene transcription, biosynthesis of neurotransmitters and nucleic acids, drivers of cell division, organ development and embryogenesis, all of which contribute to normal neural function. In poultry, a single or collective vitamin deficiency can induce neurological ailments such as peripheral neuropathies, paralysis, ataxia, areflexia, encephalopathy, opisthotonos, impaired locomotion and convulsions.